Microbial Mutagenicity Assay: Ames Test - Urvashi Vijay; Sonal Gupta; Priyanka Mathur; Prashanth Suravajhala; Pradeep Bhatnagar (Bio-Protocol, 2018)
The Microbial mutagenicity Ames test is a bacterial bioassay accomplished in vitro to evaluate the mutagenicity of various environmental carcinogens and toxins. While Ames test is used to identify the revert mutations which are present in strains, it can also be used to detect the mutagenicity of environmental samples such as drugs, dyes, reagents, cosmetics, waste water, pesticides and other substances which are easily solubilized in a liquid suspension. We present the protocol for conducting Ames test in the laboratory.